Analisis Kinerja Keuangan Menggunakan Metode Du Pont pada Bank Badan Usaha Milik Negara dan Bank Badan Usaha Milik Daerah - Nabila Aura Putri; M. Ikhwan Maulana Haeruddin; Annisa Paramaswary Aslam; Anwar Ramli; Nurman Nurman (AKUNTANSI 45, 2025)
This research intends to examine the financial capabilities of state-owned banks (BUMN) and regional-owned banks (BUMD) in Indonesia through the Du Pont Sistem Analysis approach. The study subjects include BUMN Banks such as Bank BRI, Bank BNI, Bank Mandiri, and Bank BTN, along with BUMD Banks like Bank BJB and Bank BJTM, covering a research duration of five years from 2020 to 2024. The Du Pont method is utilized as it offers an all-encompassing view of a company’s financial performance via three key financial ratios: Net Profit Margin (NPM), Total Assets Turnover, and Return On Investment (ROI). The findings of this research show that state-owned banks typically exhibited more consistent and stable performance compared to regionally owned banks throughout the analyzed period. BRI and Mandiri have consistently achieved high Net Profit Margins (NPM) by sustaining operational efficiency and enhancing credit management, leading to relatively stable earnings even amid uncertain national economic situations, especially during the COVID-19 pandemic. Additionally, the Total Asset Turnover (TATO) of government-owned banks shows greater asset utilization efficiency when compared to regionally owned banks. In contrast, banks like BJB and BJTM, which are regionally owned, demonstrated more variable performance on a yearly basis. This arises from constrained business growth, reduced asset capacity relative to state-owned banks, and heightened reliance on income from the credit sector, which is susceptible to financing risks. State-owned banks generally exhibit lower NPM and TATO ratios, leading to a suboptimal ROI in comparison to private banks.